1983
DOI: 10.1017/s009483730000751x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a conducting strand in early Silurian (Llandoverian) plants: implications for the evolution of the land plants

Abstract: Macerations of fragmented plant compressions of Silurian (Llandoverian) age yield sheets of organic material bearing ridges and depressions (interpreted as corresponding to surficial dimensions of cells), fragments of smooth walled tubular elements, and fragments of tubular elements with differentially thickened walls (“banded tubes”). A fragment of tissue (1.2 mm long), consisting of smooth walled tubes (17 ± 6.9 μm in diameter), surrounding 2–3 larger (18.8 ± 2.1 μm in diameter) banded tubes, was isolated fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 24 publications
(35 reference statements)
0
17
0
Order By: Relevance
“…Edwards & Davies, 1990;Fanning, Edwards & Richardson, 1990) and it persisted into the early Devonian. The recent demonstration of tracheids in LowerDcvonian C. pertoni confirms its vascular status (Edwards, Davies & Axe, 1992), but tracheids have not been seen in other Devonian rhyniophytoids nor in Silurian fertile axes (Edwards & Rogerson, 1976;Niklas & Smokovitis, 1983), As the Cooksonia tracheids were very small and few, failure to demonstrate them in these taxa is understandable. A growing body of evidence from late Silurian sporangia has revealed that some of the spores in the dispersed record, particularly the oldest ones (e.g.…”
Section: The Plant Evidencementioning
confidence: 96%
See 1 more Smart Citation
“…Edwards & Davies, 1990;Fanning, Edwards & Richardson, 1990) and it persisted into the early Devonian. The recent demonstration of tracheids in LowerDcvonian C. pertoni confirms its vascular status (Edwards, Davies & Axe, 1992), but tracheids have not been seen in other Devonian rhyniophytoids nor in Silurian fertile axes (Edwards & Rogerson, 1976;Niklas & Smokovitis, 1983), As the Cooksonia tracheids were very small and few, failure to demonstrate them in these taxa is understandable. A growing body of evidence from late Silurian sporangia has revealed that some of the spores in the dispersed record, particularly the oldest ones (e.g.…”
Section: The Plant Evidencementioning
confidence: 96%
“…Maceration of circular, elliptical and coalified compressions with irregular outlines, just a few millimetres in diameter from Llandovery sediments (Pratt et al, 1978) have yielded sheets of organic matter with possible cellular imprints and fragments of wefts of both smooth and ornamented tubes (Niklas & Smokovitis, 1983). In one example longitudinally aligned smooth tubes surround similarly orientated banded forms.…”
Section: Coalified Fossilsmentioning
confidence: 99%
“…Fossil spore and possibly micro-fossil records suggest that vascular plants made their appearance in the Silurian (Niklas and Smocovitis 1983 ;Kenrick and Crane 1997 ;Taylor et al 2009 ), with the Lower Devonian giving rise to a diversity of plants with transport tissues (Niklas 1985 ). Of these proto-vascular plants, the Rhyniophytes (so-named for the Early Devonian Rhynie Chert locality) are probably the best characterized.…”
Section: Xylem In Early Land Plantsmentioning
confidence: 99%
“…Such ornamented tubes are usually found within wefts dominated by associations of smooth-walled smaller tubes often showing no preferred orientation and interpreted as part of a thalloid organism (Lang, 1937;Edwards, 1982;Strother, 1988). However Lang thought that the wider tubes may have been concentrated towards the interior of the thallus, and Niklas & Smocovitis (1983) isolated a strand with longitudinally aligned banded tubes from a small thalloid compression. In contrast, Nematasketurn Burgess & Edwards, 1988 differs from the nematophyte, Prototaxites, mainly in its possession of tubes with internal annular to anastomosing thickenings.…”
Section: Ig) Fhylogenetic Significance Of Tracheary Thickeningsmentioning
confidence: 99%